DNA‐ and Field‐Mediated Assembly of Magnetic Nanoparticles into High‐Aspect Ratio Crystals. Issue 4 (9th December 2019) - Park, Sarah S.; Urbach, Zachary J.; Brisbois, Chase A.; Parker, Kelly A.; Partridge, Benjamin E.; Oh, Taegon; Dravid, Vinayak P.; Olvera de la Cruz, Monica; Mirkin, Chad A.
Abstract: Under an applied magnetic field, superparamagnetic Fe3 O4 nanoparticles with complementary DNA strands assemble into crystalline, pseudo‐1D elongated superlattice structures. The assembly process is driven through a combination of DNA hybridization and particle dipolar coupling, a property dependent on particle composition, size, and interparticle distance. The DNA controls interparticle distance and crystal symmetry, while the magnetic field leads to anisotropic crystal growth. Increasing the dipole interaction between particles by increasing particle size or external field strength leads to a preference for a particular crystal morphology (e.g., rhombic dodecahedra, stacked clusters, and smooth rods). Molecular dynamics simulations show that an understanding of both DNA hybridization energetic and magnetic interactions is required to predict the resulting crystal morphology. Taken together, the data show that applied magnetic fields with magnetic nanoparticles can be deliberately used to access nanostructures beyond what is possible with DNA hybridization alone. Abstract : DNA programmable assembly in combination with applied magnetic fields is used to direct magnetite nanoparticles into high‐aspect‐ratio superlattice crystals with various morphologies. A range of field strengths, nanoparticle core diameters, particle symmetries, and DNA lengths are explored to understand the competition between hybridization and magnetic dipole–dipole coupling interactions.